1993
DOI: 10.1021/jm00069a010
|View full text |Cite
|
Sign up to set email alerts
|

Antagonism of 1-(2,5-dimethoxy-4-methylphenyl)-2-aminopropane stimulus with a newly identified 5-HT2- versus 5-HT1C-selective antagonist

Abstract: DOM [i.e., 1-(2,5-dimethoxy-4-methylphenyl)-2-aminopropane] is a 5-HT1C/2 serotonin agonist that exerts stimulus control of behavior in animals. In order to determine if the discriminative stimulus effect of DOM is 5-HT1C- or 5-HT2-mediated, it would be informative to conduct tests of stimulus antagonism with a 5-HT1C- or 5-HT2-selective antagonist. To date, no such agents exist. Although the neuroleptic agent spiperone binds at D2 dopamine receptors and 5-HT1A serotonin receptors, (a) it displays about a 1000… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 9 publications
1
33
0
Order By: Relevance
“…Reaction of 6 with methanesulfonyl chloride in the presence of triethylamine, followed by the addition of sodium iodide, afforded the bis(2-iodoethyl)silane 7 (81 % yield). Treatment of 7 with 3-[2-(4-fluorophenyl)-1,3-dioxolan-2-yl]propylamine [12] (8) gave the cyclization product, the 4-silapiperidine 9 (50 % yield). Deprotection of 9 by treatment with hydrochloric acid afforded the title compound as the hydrochloride (sila-haloperidol hydrochloride, 1 b·HCl, 71 % yield).…”
Section: Resultsmentioning
confidence: 99%
“…Reaction of 6 with methanesulfonyl chloride in the presence of triethylamine, followed by the addition of sodium iodide, afforded the bis(2-iodoethyl)silane 7 (81 % yield). Treatment of 7 with 3-[2-(4-fluorophenyl)-1,3-dioxolan-2-yl]propylamine [12] (8) gave the cyclization product, the 4-silapiperidine 9 (50 % yield). Deprotection of 9 by treatment with hydrochloric acid afforded the title compound as the hydrochloride (sila-haloperidol hydrochloride, 1 b·HCl, 71 % yield).…”
Section: Resultsmentioning
confidence: 99%
“…More recent studies with highly selective 5-HT receptor agonists and antagonists have confirmed earlier findings and implicated 5-HT 2 receptors as the primary mechanism involved in quipazine discrimination. A variety of 5-HT 2 -selective agonists can exert stimulus control over behavior (Glennon 1991;Ismaiel et al 1993), and 5-HT 2 -selective agonists substitute for quipazine, whereas 5-HT 2 -selective antagonists readily block quipazine discrimination (Glennon et al 1983;Friedman et al 1984;Smith et al 1995). Moreover, studies have demonstrated 5-HT 2 receptor involvement in quipazine-induced suppression of schedule-controlled operant behavior in squirrel monkeys (McKearney 1990), and in quipazine-induced anorexia in rodents (Hewson et al 1988;Skukla et al 1990).…”
Section: Discussionmentioning
confidence: 99%
“…Fluorophenols can serve as synthons for the production of drugs, including enzyme inhibitors [2,3] and receptor antagonists. [4] Catecholamines and amino acids with a radiolabelled [ 18 F]-fluorophenol moiety have found applications for the in vivo imaging of amino acid metabolism [5] and protein synthesis [6] using positron emission tomography (PET). [7] Chemical methods to produce fluorophenols include diazotization/Sandmeyer decomposition with fluoroanilines, diazotization/thermal decomposition with aminophenols, alkaline hydrolysis with substituted fluorobenzene and F 2 /N 2 gas/liquid phase conversion with phenol.…”
Section: Introductionmentioning
confidence: 99%